2019
DOI: 10.1111/codi.14548
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the readability, quality and accuracy of online health information for patients with low anterior resection syndrome following surgery for rectal cancer

Abstract: Aim Management of low anterior resection syndrome (LARS) requires a high degree of patient engagement. This process may be facilitated by online health-related information and education. The aim of this study was to systematically review current online health information on LARS.Method An online search of Google, Yahoo and Bing was performed using the search terms 'low anterior/anterior resection syndrome' and 'bowel function/movements after rectal cancer surgery'. Websites were assessed for readability (eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
41
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 32 publications
6
41
2
1
Order By: Relevance
“…Previous studies have assessed the quality and readability of health information available online for various patient groups (Alsoghier, Ni Riordain, Fedele, & Porter, ; De Man et al, ; Garfinkle et al, ; Lee et al, ; San Giorgi, Groot, & Dikkers, ). Similar to the findings of this study, these studies have reported a lack of good quality health information available online.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed the quality and readability of health information available online for various patient groups (Alsoghier, Ni Riordain, Fedele, & Porter, ; De Man et al, ; Garfinkle et al, ; Lee et al, ; San Giorgi, Groot, & Dikkers, ). Similar to the findings of this study, these studies have reported a lack of good quality health information available online.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative screening tools to predict LARS are rarely used and information given to patients is often insufficient [ 207 ]. Information dedicated to patients and relatives on websites of colorectal clinics about LARS is lacking important content and material is too complex to understand [ 208 ]. Patients experience a lack of supportive care after surgery for functional complaints and do not know who to counsel [ 209 ].…”
Section: Discussionmentioning
confidence: 99%
“…Online information may allow patients to better inform themselves on this highly sensitive subject; however, the information may not always be reliable, since the quality of content is typically not monitored [7]. Additionally, patient materials are rarely written at the American Medical Association-recommended sixth-grade reading level [8].…”
mentioning
confidence: 99%